HUBUNGAN ANTARA KEKUATAN OTOT LENGAN DAN KOORDINASI MATA TANGAN TERHADAP KEMAMPUAN PASSING BAWAH BOLA VOLI pada SISWA PUTRA EKSTRAKURIKULER SMP NEGERI 40 PEKANBARU - Joni Iskandar; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine whether there is a relationship between arm muscle strength and hand eye coordination on the ability to pass under volleyball on male extracurricular students at SMP Negeri 40 Pekanbaru. The sample of this study is the male students of the extracurricular players of the 40 Pekanbaru Middle School in 18 people. The sampling technique is taken in total (total sampling) or the full sampling technique in male extracurricular students of the 18 Pekanbaru junior high school, totaling 18 people. The results of the correlation in male extracurricular male students of SMP Negeri 40 pekanbaru where the first analysis between arm muscle strength X1 and Y where rtab at a significant level ɑ (0.05) = r_count (0.91)> r_tab (0.606), means that the hypothesis is accepted and there is a relationship strong between arm muscle strength towards volleyball's under-passing ability in male students Extracurricular 40 SMP Negeri pekanbaru. From the calculation of the analysis of both X2 and Y, where r_tab at a significant level ɑ (0.05) = means r_count (0.94)> r_tab (0.606), it means that the hypothesis is accepted and there is a strong relationship between hand eye coordination on volleyball under-passing male extracurricular students at SMP Negeri 40 pekanbaru. The third analysis of the relationship of arm muscle strength (X1) hand eye coordination (X2) with the results of lower passing (Y) where rtab at a significant level ɑ (0.05) = r_count (0.96)> r_tab (0.606), it can be concluded that the relationship between (X1) and (X2) with (Y) or the relationship of arm muscle strength and hand eye coordination with lower passing results on strong interventions.Key Words: Arm Muscle Strength, Lower Coordination and Passing.